Culture and corporate voluntary reporting: A comparative exploration of the chairperson's report in India and New Zealand - Mir, M.; Chatterjee, Bikram; Rahaman, A. (Emerald Group Publishing Limited, 2009)
Purpose: The purpose of this paper is to explore the cultural underpinnings of accounting practices through a comparative analysis of India and New Zealand, using the chairperson's report, which is increasingly becoming one of the most important segments of the corporate annual report. Design/methodology/approach: The annual reports of Indian and New Zealand companies from 2001 to 2005 were selected to investigate the extent and nature of information disclosure in their chairperson's report. “Content analysis” is the main methodological orientation of the paper. Findings: The paper argues that, contrary to propositions based on Hofstede's cultural framework, Indian companies provide more disclosure in their chairperson's report than their New Zealand counterparts. This leads to the conclusion that voluntary disclosure, more generally, is a complex phenomenon and cultural variables alone may not be sufficient predictors of the voluntary disclosure practices of a country. Originality/value: Using India and New Zealand, two countries with significant cultural differences, according to Hofstede's typology, the paper extends the literature by focusing on the chairperson's report, a more recent accounting phenomenon which is gaining popularity across the globe.